2005
DOI: 10.1111/j.1747-4477.2005.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Of Patient Complaints And Signs To Histopathologic Diagnosis Of Pulpal Condition

Abstract: The correlation between the histopathologic examination of pulp biopsy specimens and patients' complaints and signs was investigated. The sensitivity, specificity and reliability of each complaint and sign, and the characteristics of pain that are associated with treatable and untreatable pulp states is proposed. Pulp specimens were obtained from teeth that required endodontic treatment. Clinical data were recorded to identify each patient's complaints. The pulp specimens were processed and the histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…In parallel, we underline the fact that the evaluation of the pathological status of the dental pulp without correlation with the clinical context seems not to yield reliable results. Similar but isolated observations were published in the literature of the ‘60s [ 8 , 11 ] and also recently [ 12 , 14 ]. Unfortunately, their scientific messages were not able to influence the strategy of pulp disease classification.…”
Section: Discussionsupporting
confidence: 86%
“…In parallel, we underline the fact that the evaluation of the pathological status of the dental pulp without correlation with the clinical context seems not to yield reliable results. Similar but isolated observations were published in the literature of the ‘60s [ 8 , 11 ] and also recently [ 12 , 14 ]. Unfortunately, their scientific messages were not able to influence the strategy of pulp disease classification.…”
Section: Discussionsupporting
confidence: 86%
“…Pulpal sensibility testing with cold combined with an electric pulp tester are accurate and reliable methods of determining pulpal vitality (92% sensitivity and 90% specificity) ( 18 ). However, when the relationship between patient complaints and histopathologic diagnosis of pulpal condition have been analyzed, results have shown that finding that pain on cold stimuli was present in 100% of patients with untreatable pulpal states (100% sensitivity) but also was present in 71% of patients with treatable pulpal states (28.6% specificity) ( 19 ). Although the pulp response to the cold does not differentiate accurately if an irreversible pulpitis already exists, in regular dental practice the cold test has validity to discriminate between vital and nonvital pulp ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that pulp testing does not always give accurate information about pulp status (Seltzer et al 1963, Dummer et al 1980, Bender 2000, Cisneros-Cabello & Segura-Egea 2005, Mej are et al 2012). However, a major advantage of EPT is its ability to make accurate comparisons of the electric response threshold value of the same tooth over time that yields important diagnostic information.…”
Section: Discussionmentioning
confidence: 99%